Impersonating Fishermen: Illegal Fishing and the Entry of Illegal Immigrants as Transnational Crime - Lewerissa, Yanti Amelia (Universitas Negeri Semarang, 2018)
Illegal fishing carried out by foreign fishing vessels (Kapal Ikan Asing, KIA) and Indonesian fishing vessels (Kapal Ikan Indonesia, KII) in Indonesian waters also causes other crimes such as the entry of illegal immigrants to Indonesia. This writing aims to assess the relationship between illegal fishing and the entry of illegal immigrants as a form of transnational crime. The research method used is normative legal research. The sources of legal material used are primary, secondary and tertiary legal materials related to writing. The technique of collecting data through library studies and analyzed qualitatively. The results of the study show that Indonesia as the largest archipelagic country in the world with 17,504 large and small islands and a length of coastline of 81,700 km 2 makes Indonesia a country with abundant marine resource potential. For this reason, many foreign naval fleets have made Indonesian waters as the main destination for their capture fisheries. This capture fishery company has more foreign ownership, the exploitation of marine resources that we own both legally and illegally. Likewise, this also happened in the Moluccas territory. As a province of the archipelago with an ocean area of ​​658,295 km 2 with a coastline length of 11,000 km 2, the Maluku Sea holds abundant potential for marine wealth. Arafura Sea is one of the fisheries management areas which is often the main destination for foreign-owned fishing vessels. These fresh fish from the Moluccas are stolen and taken away in fresh condition directly to the area of ​​origin of the perpetrators. Illegal fishing activities not only make Indonesia economically disadvantaged, but there is another problem, namely the existence of other crimes that usually follow the illegal fishing activities. One of them is the entry of illegal immigrants into Indonesian territory.